THE EFFECT OF WORK COORDINATION AND EFFECTIVENESS ON EMPLOYEE PRODUCTIVITY AT PT. UNILEVER INDONESIA - Porando Sitanggang, Edison; Rangkuti, Zulkifli; Hanaffy, Jamal (Yayasan Pendidikan Cahaya Budaya Indonesia, 2025)
This study aims to analyze the influence of coordination and work effectiveness on employee productivity at PT Unilever Indonesia. The research method used is a quantitative approach with descriptive and associative types, with a sample of 70 respondents determined using the Slovin formula. Data analysis used SPSS version 29. The results of the study indicate that coordination has a significant effect on employee work productivity, as well as work effectiveness also has a significant effect on work productivity. In addition, coordination and work effectiveness simultaneously have been shown to have a significant effect on employee work productivity. These results confirm that improving coordination and work effectiveness is necessary to boost employee productivity.